2009
DOI: 10.1042/bst0370687
|View full text |Cite
|
Sign up to set email alerts
|

From biominerals to biomaterials: the role of biomolecule–mineral interactions

Abstract: Interactions between inorganic materials and biomolecules at the molecular level, although complex, are commonplace. Examples include biominerals, which are, in most cases, facilitated by and in contact with biomolecules; implantable biomaterials; and food and drug handling. The effectiveness of these functional materials is dependent on the interfacial properties, i.e. the extent of molecular level 'association' with biomolecules. The present article gives information on biomolecule-inorganic material interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…From estimation of the size of peptide molecules using molecular dynamics (MD) software, the theoretical maximum number of peptide molecules needed to form monolayer coverage (assuming that the peptides adsorbed to the ZnO surfaces end-on/upright for maximum possible monolayer coverage) on the total surface area of ZnO rods present in an ITC experiment (based on BET analysis), was less than the amount of peptide experimentally needed to attain saturation in ITC experiments. For example, the number of unit molecules of G-12 estimated to fill a monolayer was 8.91 x 10 13 and the amount needed to reach saturation in ITC experiments was 2.46 x 10 17 . In all the interactions, the amount of peptide needed to obtain saturation was in great excess of the amount required to form monolayer coverage suggesting that dense peptide multilayers were formed on ZnO.…”
Section: Itc Study Of Interactions Of G-12 and Its Alaninementioning
confidence: 99%
See 1 more Smart Citation
“…From estimation of the size of peptide molecules using molecular dynamics (MD) software, the theoretical maximum number of peptide molecules needed to form monolayer coverage (assuming that the peptides adsorbed to the ZnO surfaces end-on/upright for maximum possible monolayer coverage) on the total surface area of ZnO rods present in an ITC experiment (based on BET analysis), was less than the amount of peptide experimentally needed to attain saturation in ITC experiments. For example, the number of unit molecules of G-12 estimated to fill a monolayer was 8.91 x 10 13 and the amount needed to reach saturation in ITC experiments was 2.46 x 10 17 . In all the interactions, the amount of peptide needed to obtain saturation was in great excess of the amount required to form monolayer coverage suggesting that dense peptide multilayers were formed on ZnO.…”
Section: Itc Study Of Interactions Of G-12 and Its Alaninementioning
confidence: 99%
“…Therefore, understanding the energetic changes that occur during peptide-inorganic interactions and correlating these to structural modifications of the inorganic materials could be the key to advancing material synthesis/design and may also reveal key principles through which material structure is controlled in nature. [15][16][17] Of specific interest, in-house studies have been carried out to understand the fundamental principles through which ZnO binding peptides (ZnO-BPs) interact with and modify ZnO growth process and morphology. 6,8,18 In a recent contribution, the mechanisms through which specific ZnO binding peptides (ZnO-BPs) interact with and modify the growth process and morphology of ZnO during solution synthesis was described.…”
Section: Introductionmentioning
confidence: 99%
“…For example, efforts to synthesize silica from precursors to replicate hierarchically organized silica-protein skeletons similar to diatoms, marine organisms, 5,11,12 and plants have shown first successes in achievable structural order. 7,9,[13][14][15][16][17] However, fundamental insight into mechanisms and control of assembly remains incomplete even though many amino acid sequences, peptides and proteins from microorganisms, cellular templates, and designed ligands were tested. 6-10, 14, 18 Therefore, better understanding of the role of the precursors, of the surface chemistry of silica formed, as well as of the competitive interactions with solvents and proteins could provide significant benefits to the rational engineering of silica-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…21 The adhesion must be rapid, strong, tough, and the thickness of the adhesion layer is usually within several to tens of nanometers. Inspired by the bioadhesion phenomenon and the composition of adhesive proteins in mussels, Messsersmith 52 found that dopamine could form multifunctional polymer coatings through a simple dip-coating of objects in an aqueous solution under mild conditions.…”
Section: Synthesis Of Silica-based Materials Through Synergy Between mentioning
confidence: 99%